Higher Education Graduates Competencies: Evidence from Literature Review - Wijil Nugroho; Leo Alexander Tambunan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The aim of this paper is to review determinants of graduates’ competencies of Indonesian Higher Education Institution. Accreditation bodies also appear to measure quality of education through the contributions made towards employability. This research was conducted with the aim of identifying the skills needed by employers in various countries, various definitions related to competencies, previous research conducted in various countries related to job skills requirements and recommendations. The study is based on a literature study of educational reports, empirical and theoretical research papers. Research conducted in Indonesia and other countries as well as comparing situations between countries is also summarized in this paper. Review findings reveled that competencies definitions, employer expectation and requirement differ according to different countries. Employers' needs and also the learners' competency enhancement capabilities should be taken into account in formulating future competency assessments. This study summaries that universities should identify competency sets that will best serve for the future labor market and align programs to meet those who needed.